1997
DOI: 10.1155/1997/869747
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome (Prosome) Subunit Variations during the Differentiation of Myeloid U937 Cells

Abstract: 20S proteasomes (prosomes/multicatalytic proteinase) are protein particles built of 28 subunits in variable composition. We studied the changes in proteasome subunit composition during the differentiation of U937 cells induced by phorbol‐myristate‐acetate or retinoic acid plus 1,25‐dihydroxy‐cholecalciferol by western blot, flow cytometry and immuno‐fluorescence. p25K (C3), p27K (IOTA) and p30/33K (C2) subunits were detected in both the nucleus and cytoplasm of undifferentiated cells. Flow cytometry demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…By comparing ␣-p25 with ␣-p27 and a third proteasomal core antibody against the ␣6 subunit, 62A32, we have previously shown that both bands are proteasome related and that these antibodies can detect proteasomal core antigens in Western blotting (Kleijnen et al, 2000;Walters et al, 2002). Most likely, the two ␣-p25 bands represent different splice variants that may depend on the particular cell line one uses, because a similar situation has been reported for the 62A32 antibody (Silva Pereira et al, 1992;Henry et al, 1997). It was discovered that the proteasomal core antigens could be preferentially eluted from the beads with a wash in NP-40 lysis buffer supplemented with 150 mM NaCl (the GST proteins remain on the beads), allowing for clean Western blotting.…”
Section: Proteasome Pull Down From Cell Lysatementioning
confidence: 61%
“…By comparing ␣-p25 with ␣-p27 and a third proteasomal core antibody against the ␣6 subunit, 62A32, we have previously shown that both bands are proteasome related and that these antibodies can detect proteasomal core antigens in Western blotting (Kleijnen et al, 2000;Walters et al, 2002). Most likely, the two ␣-p25 bands represent different splice variants that may depend on the particular cell line one uses, because a similar situation has been reported for the 62A32 antibody (Silva Pereira et al, 1992;Henry et al, 1997). It was discovered that the proteasomal core antigens could be preferentially eluted from the beads with a wash in NP-40 lysis buffer supplemented with 150 mM NaCl (the GST proteins remain on the beads), allowing for clean Western blotting.…”
Section: Proteasome Pull Down From Cell Lysatementioning
confidence: 61%
“…Anomalies in the ubiquitin‐proteasome pathway have been described in various pathologic settings, including malignant disease,18 and proteasome inhibitors can induce tumor regression in animal models 19. Along with others, we have published modifications in the intracellular expression and subunit composition of proteasome in leukemic cells4–8 as well as abnormal proteasome levels in tumor and stromal cells in some patients of breast carcinoma 20. Moreover, gene expression of the proteasome subunit iota is increased in patients with ALL and decreased in patients with AML 21…”
Section: Discussionmentioning
confidence: 96%
“…In 1990, Kumatori et al4 first demonstrated an abnormally high expression level of proteasomes in human leukemic cells. We subsequently published findings that, in some examples of neoplastic differentiation, the amount and subunit composition of cell proteasomes indeed varied 5–8. Proteasomes can be detected and measured on the cell surface of lymphocytes9 and in cell culture supernatants or patient serum 10.…”
mentioning
confidence: 99%
“…13 PMA was shown to diminish the inclusion of the p30/33K proteasome subunit and the amount of p25K and p27K, 35 but whether this indeed increases proteasome activity is not yet known. There are conflicting data regarding the effect of PMA activation on lysosomal enzyme activity.…”
Section: Pma Effects On Microglial Proteolytic Systemsmentioning
confidence: 99%